2015
DOI: 10.1111/1755-5922.12122
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Versus Placebo in Improvement of Endothelial Dysfunction: A Meta‐Analysis of Randomized Clinical Trials

Abstract: SUMMARYAims: The possible effect of vitamin D administration in humans on endothelial dysfunction (ED) still remains undetermined. The current meta-analysis was performed to evaluate if vitamin D could improve ED. Methods: Randomized, double-blind, and placebo-controlled clinical trials were identified by systematic search of the PubMed, the Cochrane Library, the Web of Science and the Scopus data bases, as well as different reviews and clinical trials articles. A random effects model was used to calculate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 43 publications
(71 reference statements)
3
15
0
1
Order By: Relevance
“…In line with our results, Wu‐Wong et al have reported that paricalcitol can improve endothelial‐dependent relaxation in uremic rats independent from effects on PTH serum concentration 16, 17. Recently, randomized clinical trials conducted in patients with CKD also demonstrated that treatment with active vitamin D leads to significantly favorable changes in endothelial function 18, 19, 33, 34, 35…”
Section: Discussionsupporting
confidence: 91%
“…In line with our results, Wu‐Wong et al have reported that paricalcitol can improve endothelial‐dependent relaxation in uremic rats independent from effects on PTH serum concentration 16, 17. Recently, randomized clinical trials conducted in patients with CKD also demonstrated that treatment with active vitamin D leads to significantly favorable changes in endothelial function 18, 19, 33, 34, 35…”
Section: Discussionsupporting
confidence: 91%
“…Vitamin D 3 supplementation reduces all-cause mortality in elderly people [3], but a causal benefit for CVD-specific mortality has not been established. Results from studies examining CVD effects of vitamin D supplementation have been inconsistent [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It hampers ROS formation in cardiomyocytes, but its effect on endothelium needs further evaluation [92]. Some studies indicated a beneficial effect of vitamin D supplementation on endothelium by an increase in FMD of the brachial artery [93]. Vitamin D may be particularly useful in an oncological setting due to its demonstrated in vivo and in vitro antiangiogenic properties [94].…”
Section: Antioxidant Therapymentioning
confidence: 99%
“…Vitamin D may be particularly useful in an oncological setting due to its demonstrated in vivo and in vitro antiangiogenic properties [94]. According to meta-analysis [93] vitamin D supplementation significantly decreases mortality due to cancer and CV events. The effect of vitamin D on endothelium still needs further evaluation, especially to establish a proper supplemented dosage.…”
Section: Antioxidant Therapymentioning
confidence: 99%